2017
DOI: 10.1055/s-0043-111899
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Angiogenesis: Cause of Abnormally Thin Endometrium in Subfertile Patients?

Abstract: Introduction This study investigated subfertile patients with abnormally thin endometrium after infertility treatment. As they had adequate serum concentrations of hormones, an endometrial factor for subfertility was suspected. Methods To elucidate the cause of subfertility, endometrial biopsies were taken in each patient in the late proliferative and mid-secretory phases of one menstrual cycle. Endometrial biopsies from women with normal menstrual cycles and confirmed fertility who were undergoing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 73 publications
(96 reference statements)
0
30
0
5
Order By: Relevance
“…It starts with the apposition of the blastocyst at the uterine endometrium and then attachment to the endometrial surface epithelium . Several studies have shown that a thin endometrium adversely affects the pregnancy rate in IVF …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It starts with the apposition of the blastocyst at the uterine endometrium and then attachment to the endometrial surface epithelium . Several studies have shown that a thin endometrium adversely affects the pregnancy rate in IVF …”
Section: Discussionmentioning
confidence: 99%
“…9 Several studies have shown that a thin endometrium adversely affects the pregnancy rate in IVF. [10][11][12] After surgical abortion, inflammation can occur in both the endometrium and the oviduct. Endometritis is chronic inflammation of the inner lining of the uterine cavity, and leads to abnormal uterine bleeding, recurrent spontaneous abortion, and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired angiogenesis in COH rats is expected to lead to defective development of the endometrium 44 and thus influence the morphologic feature of uterus. To verify this expectation, a morphometry analysis was performed for the HE-stained sections.…”
Section: Btg and Kw Respectively Improve The Uterus Index And Incmentioning
confidence: 99%
“…Эстроген и прогестерон играют главную роль в формировании сосудистого русла, однако механизмы их воздействия до конца непонятны [3]. Эстрогены стимулируют рост эндометрия, активируя образование новых сосудов [6] и миграцию гладких миоцитов [7]. Повышение плотности сосудов в эндометрии обнаружено у женщин с гиперплазией эндометрия, связанной с гиперэстрогенемией [8].…”
Section: Remodeling Of Endometrial Vascular System In Women Of Reprodunclassified